THE IMPORTANCE OF A MONOPOLISTIC COMPETITIVE MARKET SITUATION IN A MARKET ECONOMY (British Journal of Global Ecology and Sustainable Development, 2023)
This article will consider scientific and practical data on the importance of a monopolistic competitive market situation in a market economy. The data obtained will be analyzed and scientifically based proposals and judgments will be given on their basis. The article examines the dominance of monopoly in the market, prices for consumer goods, the role of antimonopoly legislation.